MR Features of Cerebral Aspergillosis in an Immunocompetent Patient: Correlation with Histology and Elemental Analysis - Phuttharak, Warinthorn (AJNR Am J Neuroradiol, 2005)
Summary: We report an unusual case of cerebral aspergillosis in a young immunocompetent patient who also had dissemination to other end organs. The patient presented with a large mass in the left cerebral hemisphere. Elemental analysis of biopsy specimens revealed elevated levels of iron, magnesium, zinc, calcium, chromium, and nickel that correlated with a peripheral rim of hypointensity on T2-weighted images.